2017
DOI: 10.5812/whb.14171
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Educational Stress Management on Job stress of Operating Room Nurses at Hospitals Affiliated to Shiraz University of Medical Sciences During Year 2016: A Randomized Controlled Clinical Trial

Abstract: Background: Job stress is a psycho-social stress that is created as a result of harsh working conditions and effects individuals' performance and physical and mental health. In fact, many mental and psychological health problems are directly related to job stress. Stress at the workplace could even create disabilities in some cases. The nature of work at hospitals, especially operating rooms, generates a lot of stress and tension for the staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…To enhance well-being, implement empowering programs and interventions that focus on promoting healthy lifestyle behaviors, including physical activity, meditation, training courses, mental health counseling tailored for women, and psychological group meetings. The study Studies suggested adapting and controlling psychological pressures on women [ 39 , 40 ], including group therapy training sessions to identify stressful situations in the work environment and provide them with the necessary coping tools/strategies [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…To enhance well-being, implement empowering programs and interventions that focus on promoting healthy lifestyle behaviors, including physical activity, meditation, training courses, mental health counseling tailored for women, and psychological group meetings. The study Studies suggested adapting and controlling psychological pressures on women [ 39 , 40 ], including group therapy training sessions to identify stressful situations in the work environment and provide them with the necessary coping tools/strategies [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…adapts and control the psychological pressures on them and help to reduce them [29,30]. Seyyed Moharrami's study also showed that holding group therapy training sessions helped the participants to identify stressful situations in the work environment and provide the necessary situations to deal with them [31].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Studies have shown that management strategies are used to empower and support nurses so that they can cope with and adapt to stressful situations effectively, i.e., can help them control and reduce stress. [ 38 39 ] Furthermore, group therapy studies have revealed that holding training sessions helped participants to identify situations that are stressful in the workplace and set the ground for dealing with them. [ 40 ]…”
Section: Discussionmentioning
confidence: 99%